Improving Character Makeup Skills for the Ebeg Group of Mega Laras Tanjunganom, Rakit, Banjarnegara, Indonesia - Handayani, Langlang; Darsono, Teguh; Sunarno, Sunarno; Haryono, Slamet; Utina, Usrek Tani; Maulana, Haydnn Caesha; Halim, Musa Abdul; Pangestu, Iklas Adi; Putri, Nabila Rakha (Universitas Negeri Semarang, 2025)
Dancers’ makeup in a performance is an attraction for the community of connoisseurs and observers of the Ebeg. The Mega Laras group in Tanjunganom, Rakit, Banjarnegara was plagued by problems with the makeup of its performers in staging performances, caused by the lack of knowledge and skills of the dancers and makeup artists. With full support from the village government and all group members to conserve Ebeg as an Indonesian cultural heritage, Universitas Negeri Semarang through its community service team provided a solution through facilitation-based action learning model training. The purpose of this activity was to improve the makeup skills of the group members, with main stages of implementation of preparation, training, and result analysis. The preparation included coordinating with partners about the place and time of the activity, and team coordination regarding technical implementation. The training phase included planning, workshop, and mentoring. During the training, a set of tools and makeup materials were distributed to partner. Analysis of the overall activity showed that 80% of participants demonstrated significant skill improvement after the training. The community service activity supports Sustainable Development Goal (SDGs) 4, namely Quality Education, for providing lifelong learning opportunities for the traditional arts practitioners.